On Testing the Significance of Differences in Population Structures Based on Small Sample Sizes - Kończak, Grzegorz; Kosińska, Martyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2024)
Objective: This article examines the significance of differences in the structures of two or more populations. Various measures of structural similarity are presented in the literature, but no statistical tests are available to confirm the statistical significance of differences in the structures being investigated. The aim of the article is to propose a statistical test to confirm the existence of significant differences in structures based on data from contingency tables. Research Design & Methods: Literature review. The statistical test proposed is based on the idea of Fisher’s exact test. Findings: The test is applied to the results of original research on the participation of active internet portal users in cultural events before and during the COVID-19 pandemic. Implications / Recommendations: The method allows for testing the significance of differences in the structures of two or more populations. Inference can be made based even on small size samples. Contribution: Comparing structures in populations is common in economic research. The statistical test described herein contributes to knowledge on the indicator of structural similarity.